Optimal Utilization of Renewable Power Production by Sharing Power among Commercial Buildings: Case Study of Griffith University - Amin, Uzma; Hossain, M.J.; Lu, J.; Fernandex, E. (2018)
Advancements in smart-grid technology such as the development of a bi-directional communication infrastructure and smart metering provide an opportunity to reduce energy cost by sharing renewable energy among buildings. A proactive building equipped with renewable energy sources (RESs) can share surplus renewable power (SRP) with neighboring traditional buildings (without RESs) for the optimal utilization of RESs. In this paper, the interaction of a proactive building with neighboring traditional buildings in the context of power sharing based on generation and load demand is considered. Within a given time horizon divided into multiple time steps in which generation and load demand occurs, the proactive buildings may experience a power surplus or deficit. While any deficit can be obtained from the utility grid, the proactive building may consider sharing/selling its unused power with neighboring buildings. An algorithm is developed to manage SRP based on price signals, RESs' production and load demand. The developed algorithm is tested using real-time load and generation data of different buildings situated in Griffith University, Australia. A cost-benefit analysis is also carried out using current electricity charges to show the cost effectiveness of power sharing.